2022
DOI: 10.3389/fonc.2022.939646
|View full text |Cite
|
Sign up to set email alerts
|

Ononin Shows Anticancer Activity Against Laryngeal Cancer via the Inhibition of ERK/JNK/p38 Signaling Pathway

Abstract: BackgroundLaryngeal cancer is a type of head and neck tumor with a poor prognosis and survival rate. The new cases of laryngeal cancer increased rapidly with a higher mortality rate around the world.ObjectiveThe current research work was focused to unveil the in vitro antitumor effects of ononin against the laryngeal cancer Hep-2 cells.MethodologyThe cytotoxic effects of ononin against the laryngeal cancer Hep-2 cells and normal HuLa-PC laryngeal cells were studied using an 3-(4,5-dimethylthiazol-2-yl)-2,5-dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…In addition, ononin, an active chemical in DBT, demonstrated antitumorigenic properties. This result was consistent in accordance with Ye et al (2022), who reported that ononin treatment significantly inhibited the Hep-2 cell viability and JNK/ERK/p38 axis, resulting in a remarkable antitumor effect. Hence these findings suggest that ononin in DBT synergizes with a chemotherapeutic drug to promote anti-CRC cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, ononin, an active chemical in DBT, demonstrated antitumorigenic properties. This result was consistent in accordance with Ye et al (2022), who reported that ononin treatment significantly inhibited the Hep-2 cell viability and JNK/ERK/p38 axis, resulting in a remarkable antitumor effect. Hence these findings suggest that ononin in DBT synergizes with a chemotherapeutic drug to promote anti-CRC cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…From the MTT data, we found only ononin presented at 1 μM was capable of inhibiting HT‐29 cell viability (Figure 9b). In fact, ononin was found to possess antiangiogenic properties and to inhibit the proliferation of different cancer cells both in vitro and in vivo (G. Gong & Zheng, 2021; Gu et al, 2021; Ye et al, 2022). Here, we demonstrated colony formation and anti‐tumor cell proliferation on cultured HT‐29 cells (Figure 9b–e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis is the main cause of clinical manifestations; however, the underlying mechanisms involved in metastasis and chemoresistance in the development of osteosarcoma remain unclear. Ononin is an active principle mostly found in fruits and vegetables that possesses several biological activities including anticancer properties [26]. Currently, no comprehensive study has been conducted on ononin and osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive role and the related synergistic mechanisms of AR with cisplatin on laryngeal squamous cell carcinoma have also been well established [ 37 ]. Ononin is an active principle primarily found in AR that possesses various pharmacological properties including anticancer activities [ 38 ]. To date, there is no study related to the synergistic effects of ononin and PTX.…”
Section: Discussionmentioning
confidence: 99%